Assessing the translation of collocations in literary texts based on Juliane House’s model (1997) of translation quality assessment - Obeidat, Adham Mousa; Ayyad, Ghada Rajeh (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of this study was to assess the translation of collocations from Arabic into English in literary texts, which are considered as a rich source of culture and fixed expressions. The methodology of this study is a descriptive- interpretive analysis of the source text (ST), which is the Arabic novel “Awlad Hartna” and the target texts (TTs), which are the English translations “Children of Gebelawi” and “Children of the Alley”. The author applied House’s (1997) model of translation quality assessment. The analysis was divided into two sections, (1) analyzing the ST and TTs according to their register and genre to find the overt errors, and (2) examining the translation of collocations to find the covert errors. The result of the study revealed that that the two translations have many mismatches at the level of field, tenor and mode, such as the lexical, cultural, linguistic and syntactic mismatches. The findings also reveal that translators have committed 106 collocational errors which were divided into four categories: not translated, slight change in meaning, significant change in meaning and distortion of meaning. The findings of the study have pedagogical implications for translators in general, translators of literature, translations students and teachers.